EFFECT OF SHEEP MANURE EXTRACT ON THE GROWTH AND NUTRIENTS CONTENT OF TOMATO SEEDLINGS - & AL-Sulaimawi, Al-A’amry (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The experiment was conducted under shading (with the aid of Saran) condition on a nursery managed by the Baghdad Mayoralty during the season of 2014-2015 to study the effect of composed sheep manure extract on the growth and leaf nutrients content of tomato seedlings var. Wijdan. The experiment was composed of 6 treatments included the extract of sheep manure by hot (425C)and lmbient(205C) temperature water .The extract was diluted to the half by water and foliar applied to seedlings (multible application) or to the soil . Treatments also included the application of NPK chemical fertilizers as recommended and a control treatment through applying distilled water as foliar .The experiment was designed according to the randomized complete block design (RCBD) with three replications and means were compared using least significant differences (LSD) test at 5% level of significance. The results showed recommended chemical fertilization gave the most significant increase in terms of number of leaves, plant height, shoot dry weight, root length, and root dry weight, which were, 6.33 leaf.plant-1, 23.83 cm.plant-1, 0.711 g.plant-1, 26.08 cm.plant-1, and 0.192 g.plant-1 respectively .The treatments of hot water extracted sheep manure compost show significant effect compared to control treatment. In addition, chemical treatment significantly increased N, P, and K concentration in leaf tissue. Mg and Ca concentration were higher in hot extract treatment and chemical treatment with no differences between them . treatments of lmbient extract gave a results less than chemical treatment in all indicates and less than treatments of hot extract in some indicates , while the control treatment gave a less results in this study.